2019
DOI: 10.31031/jbb.2019.02.000532
|View full text |Cite
|
Sign up to set email alerts
|

Kombucha and Kefir are Foods of the 21st Century: A Opinion

Abstract: Kefir is a fermented milk product having slight acidic taste, carbonation, and aroma good. The kefir beverage contains a specific mixture of microorganisms (lactic bacteria, acetic bacteria e yeast) that reside in symbiotic manner in a kefiran polysaccharide matrix. Kefir grains (Figure 1) can be characterized as small cauliflower florets, having a length of 10-40mm, irregularly shaped, white to yellowish in color, having firm texture and slimy appearance. The kefir microorganisms have a capacity to produce or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Another way to nurture a healthy gut is to consume foods that contain beneficial microorganisms (probiotics) and prebiotics. This includes the symbiotic foods, such as yogurt [25;26], kefir [ 27 , 28 ] and kombucha [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to nurture a healthy gut is to consume foods that contain beneficial microorganisms (probiotics) and prebiotics. This includes the symbiotic foods, such as yogurt [25;26], kefir [ 27 , 28 ] and kombucha [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Certainly, future clinical approaches are needed to ascertain their effectiveness in improving menthal disorders resulting from the evolution of COVID-19 outbreak. However, some potential strategies include the use of probiotic foods and natural, which have reports in the scientific literature of their numerous probiotic and nutritional benefits, such as “kefir” and “kombucha” [ 27 - 29 , 30 , 57 - 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the action of probiotic microorganisms on the host immune system have been carried out for some time [1][2][3][4][5][6][7][8][9][10][11][12][13][14][27][28][29][30][31]. Recent and non-recent bibliographies, most reporting studies with lactic acid bacteria, have shown that probiotics have an immunostimulant effect in animals and humans, although the mechanisms by which this occurs are not yet fully understood [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Kefir Probiotic Microorganisms In Immunomodulatory Activitymentioning
confidence: 99%
“…Probiotics are live microorganisms capable of preventing and controlling gastro-intestinal issues and balancing the immune system [ 9 , 10 , 11 , 12 , 13 , 14 ]. They also combat allergies, aid in de-toxification, and regulate the body for better nutrient and vitamin absorption [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation